The silent crisis: a review on epidemiology of burns and home safety challenges in Eastern India - Sahu, Ranjit Kumar; Jena, Harapriya; Sahu, Pragati; Sahu, Sabita; Pati, Hemalata (International Journal Of Community Medicine And Public Health, 2025)
Burns can represent some of the most severe injuries globally, posing a significant public health issue and sparking widespread health concerns, especially in low- and middle-income nations. This review examines the epidemiology of burns and the related home safety issues in Eastern India, an area characterized by varied socio-economic and cultural factors. Burns rank among the primary causes of illness and death, with a disproportionate impact on women, children, and the elderly. The research investigates the occurrence, risk factors, and socio-cultural influences of burn injuries, emphasizing the shortcomings in preventive strategies and access to healthcare. Living conditions in Eastern India, marked by hazardous cooking methods, cramped spaces, and inadequate fire safety knowledge, significantly increase the incidence of burn injuries. The review additionally examines current policies, health interventions, and community-centered initiatives focused on burn prevention and treatment, identifying critical areas for improvement. Highlighting the importance of a multi-sectoral strategy, this paper promotes improved public health initiatives, such as community awareness, infrastructure enhancements, and reinforced healthcare systems, to address the unnoticed crisis of burns in Eastern India.